Pengaruh Kualitas Pelayanan Pemandu Wisata Terhadap Keinginan Berkunjung Kembali Wisatawan Di Daya Tarik Air Terjun Nyarai Lubuk Alung - Shadiqatil Aqwal; Feri Ferdian (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research start with the service quality problem regarding those who wish to visit again. This research employed a descriptive research design using quantitative data. This research used both primary and secondary data sources. Tourists at the Nyarai Lubuk Alung Waterfall tourist attraction make up the research population. Using non-probability sampling techniques, the research sample consisted of 276 consumers. Purposive sampling research is the type that is carried out. A Likert scale questionnaire that has gone through validity and reliability testing is used as a collection for data tool and then processed with SPSS 25.00. The results of this research shown that service quality is in the quite agree category, namely 51.81%. Furthermore, the variable desire to visit again is in the agreed category, namely 35.51%. The impact of service quality (X) influences the desire to visit again (Y), with a score of 11.1% and 88.9% influenced by other factors. Additionally, the results of the multiple linear regression analysis yielded a t value of 0.450 with sig. 0.000 < 0.05 and a calculated F value of 1.203 with sig. 0.000 < 0.05, indicating a significant effect of the service quality variable on the desire to return.